AI-Driven Creativity: The Role of Generative Models in Event Theme and Design Conceptualization - HULEKAL, Rachita Pradeep; AS, Shravya (Journal of Environmental Management and Tourism, 2025)
This study examines how generative AI influences creativity in event theme development and design conceptualization. It explores how AI affects ideation, originality, efficiency, and ethical decision-making within event management. An integrative review of academic and industry literature from 2021–2025 was conducted across event design, creative industries, and AI research. A qualitative thematic analysis synthesised insights on generative models, human - AI co-creation, and design workflows, forming the basis for a conceptual framework. Results indicate that generative AI accelerates ideation, visualization, and early-stage prototyping, allowing designers to explore a wider range of creative directions in less time. Human - AI collaboration enhances creativity but may also narrow stylistic diversity when prompts or datasets lack cultural depth. Ethical challenges persist around authorship attribution, data provenance, and cultural bias. The study emphasizes that AI is most effective when positioned as a co-creator that complements human intuition and contextual judgement. This study is among the first to focus specifically on generative AI within event design. It offers a conceptual model of human - AI co-creation and identifies professional, educational, and regulatory implications for integrating AI into creative workflows. The study is based on secondary data; future empirical research is needed to validate the proposed framework.